THE SUSTAINABILITY ASSESSMENT OF COMMUNAL WASTE WATER TREATMENT PLANT (WWTP) IN INDONESIA: CASE STUDI COMMUNAL WWTP IN SLEMAN REGENCY, YOGYAKARTA, INDONESIA - Dwi Saputri; Fajar Marendra; Agus Prasetya; Ahmad Tawfiequrrahman Yuliansyah (Konversi, 2021)
Wastewater contains pollutants that can disturb the balance of the ecosystem in the form of health problems, water quality degradation and others. According to Said, (2008) the problem experienced in almost all cities in Indonesia is wastewater pollution. The purpose of this study is to determine the distribution of conditions and performance values, factors that influence the conditions and performance of Communal WWTPs in Sleman Regency Yogyakarta. The method used in this study is an interview with the help of guidelines to respondents who have been determined. The location of the sample collection was determined by the stratified random sampling method based on the District and Village for the decision of data collection at 30 Communal WWTPs of Sleman Regency. The results of the interview are processed by the Likert scoring method and then drawn with the Radar Chart. The factors that influence the conditions and performance of Communal WWTPs are then obtained from the ranking of the criteria for the conditions and performance of Communal WWTPs that have been calculated. The results showed that overall Communal WWTPs in Sleman Regency had conditions and performance with a value of 2.98 which was included in the interval of value 3 with a fairly good category. This value consists of the value of the technical aspect of 3.52 with a very good category, the value of the environmental aspect of 2.94 with a fairly good category, and the value of the socio-economic aspect of 2.48 with a rather poor category. Factors that influence the condition and performance of Communal WWTPs in Sleman Regency whose value is still less than expected are the maintenance of facilities with a value of 2.27, the load of wastewater with a value of 2.43, the institutional value of 2.47, and the management performance monitoring program with a value of 2.50 which falls into the rather poor value category.